2020
DOI: 10.3390/su13010093
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility and Sustainability of Hybrid Energy Systems for a Cement Factory in Oman

Abstract: Diesel generators are being used as a source of electricity in different parts of the world. Because of the significant expense in diesels cost and the requirement for a greener domain, such electric generating systems appear not to be efficient and environmentally friendly and should be tended to. This paper explores the attainability of utilizing a sustainable power source based on a cross-breed electric system in the cement factory in Salalah, Oman. The HOMER software that breaks down the system setup was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“… 69 Among the three hybrid energy systems considered in this study, the PV/GS/B, PV/B, and GS have COE values of 0.1550, 0.1500, and 0.1655, respectively. Wesam et al 57 reported that the higher the solar radiation, the more energy is generated through the renewable energy sources, the lower the NPC and COE. When the temperature and solar radiation are high in a given location, the energy generation appears predominantly high due to the association between solar radiation and the energy generated from the PV.…”
Section: Economic Assessment Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 69 Among the three hybrid energy systems considered in this study, the PV/GS/B, PV/B, and GS have COE values of 0.1550, 0.1500, and 0.1655, respectively. Wesam et al 57 reported that the higher the solar radiation, the more energy is generated through the renewable energy sources, the lower the NPC and COE. When the temperature and solar radiation are high in a given location, the energy generation appears predominantly high due to the association between solar radiation and the energy generated from the PV.…”
Section: Economic Assessment Resultsmentioning
confidence: 99%
“…HOMER software was used in our recently published study which demonstrates the validity of the model used in this present study. 57 In the software, input parameters are added and the outputs analyzed as part of the feasibility study. Moreover, HOMER’s outputs and results are widely accepted in recent relevant researches.…”
Section: Methodsmentioning
confidence: 99%
“…They are commonly used in renewable energy projects as life-cycle economic indexes. The life-cycle cost of the system is represented by the NPC, which is determined using [52,53]:…”
Section: Economic Mathematical Modelsmentioning
confidence: 99%